A stiffness reduction method for the in-plane design of stainless steel members and frames according with EN 1993-1-4. (15th February 2022) - González-de-León, Isabel; Arrayago, Itsaso; Real, Esther; Mirambell, Enrique
Highlights: A Stiffness Reduction Method based on the future EN 1993-1-4 provisions is developed. Stiffness reduction factors for austenitic, ferritic and duplex RHS columns and beams are proposed. A combined stiffness reduction factor for stainless steel RHS beam-columns subjected to different load schemes is presented. Application examples of the proposed method to austenitic RHS planar frames are shown. The assessment of the proposal against other stiffness reduction design methods is provided. Abstract: Current design standards for stainless steel such as ASCE 8-02 and EN 1993-1-4 prescribe provisions for the design of cross-sections and members that account for material nonlinearities and strain hardening, although these features are not considered in the global design of structures. Recent studies have highlighted the need of accounting for material nonlinearities in order to design efficient and safe stainless steel structures, and it is expected that the forthcoming versions of the standards will incorporate updated rules for the global design of these structures. To contribute to this field, this paper presents a Stiffness Reduction Method (SRM) for the in-plane design of stainless steel members and frames with stocky sections based on the prescriptions given in the next version of EN 1993-1-4. The proposed approach predicts the ultimate capacity and internal forces in stainless steel structures by performing a second-order elastic analysis in which the stiffnesses of the members are reduced by a set of factors defined in this paper to account for the effect of the spread of plasticity, residual stresses and member imperfections. The accuracy of the presented method is assessed for individual stainless steel structural members (columns, beams, and beam-columns) with different cross-sections and material properties, and for austenitic stainless steel portal frames, against numerical results obtained from nonlinear analyses conducted on finite element models. A comparison between the proposed approach and the Direct Analysis Method prescribed in the upcoming AISC 370 Specification is also provided, showing that the results are comparable in the two approaches.